Harnessing Digital Skills For Academic Success: Unveiling The Power of Learning Motivation in Computational Thinking and Tech Integration - Annajmi Rauf; M. Miftach Fakhri; Fathahillah Fathahillah; Dewi Fatmarani Surianto; Fadhlirrahman Baso; Fitria Arifiyanti; Stephen Amukune (Online Learning In Educational Research (OLER), 2024)
The workforce's demand for critical thinking and innovation highlights the need to improve students' problem-solving skills, thus encouraging educational institutions to adopt technology-based strategies for an engaging learning environment. Previous studies have explored the relationship between learning motivation and academic outcomes and the role of technology and web-based media in improving problem-solving skills. However, limited research has comprehensively examined the interaction between computational thinking, technology integration, learning motivation, and student performance. This study aims to examine how Computational Thinking (CT) and Technology Integration (TI) influence Learning Motivation (LM) and Student Performance (SP), providing insights into optimizing digital skills for academic success in the digital age. Data were collected from 426 respondents' university students in Indonesia randomly. A questionnaire with a 5-point Likert scale consisting of several variables such as Computational Thinking, Technology Integration, Learning Motivation, and Student Performance were used in this study. Then, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to check the measurement and assessment model. The results showed that CT and TI positively and significantly impacted LM and SP. In addition, LM serves as an important mediator, strengthening the influence of CT and IT on academic outcomes. Specifically, technology integration has a greater impact on LM than CT, while LM significantly improves SP. This study presents a detailed framework for educators to enhance learning experiences by integrating digital skills and fostering student motivation. The findings offer practical implications for developing effective educational strategies that meet the changing demands of the digital age. Future research is recommended to investigate the long-term effects of CT and IT in various educational environments.